EUC News : clubblad voor leden van 'The European Uniform Club'. (Schoten : EUC, 1980)
Fonds Suzan Daniel (FSD)
F/02/016 Archief Roger Vertongen
Periodiciteit : tweemaandelijks (?)
Redactie : Postbus17, 2120 Schoten
Nederlands
Periodiek